E3 ubiquitin ligases in the acute leukemic signaling pathways - Zhan, Qianru; Zhang, Heyang; Wu, Boquan; Zhang, Naijin; Zhang, Lijun (Frontiers in Physiology, 2022)
Acute leukemia is a common hematologic tumor with highly genetic heterogeneity, and many factors are involved in the pathogenesis and drug-resistance mechanism. Emerging evidence proves that E3 ubiquitin ligases participate in the acute leukemic signaling pathways via regulating substrates. This review summarized the E3 ligases which can affect the leukemic signal. It is worth noting that the abnormal signal is often caused by a deficiency or a mutation of the E3 ligases. In view of this phenomenon, we envisioned perspectives associated with targeted agonists of E3 ligases and proteolysis-targeting chimera technology. Moreover, we emphasized the significance of research into the upstream factors regulating the expression of E3 ubiquitin ligases. It is expected that the understanding of the mechanism of leukemic signaling pathways with which that E3 ligases are involved will be beneficial to accelerating the process of therapeutic strategy improvement for acute leukemia.